2015
DOI: 10.1155/2016/6532860
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Isoforms and Leptin Impact on Rheumatoid Adipose Mesenchymal Stem Cells Function

Abstract: Adiponectin and leptin have recently emerged as potential risk factors in rheumatoid arthritis (RA) pathogenesis. In this study we evaluated the effects of adiponectin and leptin on immunomodulatory function of adipose mesenchymal stem cells (ASCs) derived from infrapatellar fat pad of RA patients. ASCs were stimulated with leptin, low molecular weight (LMW) and high/middle molecular weight (HMW/MMW) adiponectin isoforms. The secretory activity of ASCs and their effect on rheumatoid synovial fibroblasts (RA-FL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…This means that HMW both triggers inflammation and stimulates the release of IL-6 and IL-8, which is associated with pro-destructive effects in RA FLS [127]. The secretion of TGFβ, IL-6, IL-1Ra, PGE 2 , IL-8, and VEGF was considerably increased in HMW-treated RA-adipose mesenchymal stem cells but not in LMW-treated cells [128]. Furthermore, the ratio of three full-length adiponectin isoforms was compared in the serum of RA patients.…”
Section: Issues Related To Hmw: Pro-inflammatory or Anti-inflammatorymentioning
confidence: 94%
“…This means that HMW both triggers inflammation and stimulates the release of IL-6 and IL-8, which is associated with pro-destructive effects in RA FLS [127]. The secretion of TGFβ, IL-6, IL-1Ra, PGE 2 , IL-8, and VEGF was considerably increased in HMW-treated RA-adipose mesenchymal stem cells but not in LMW-treated cells [128]. Furthermore, the ratio of three full-length adiponectin isoforms was compared in the serum of RA patients.…”
Section: Issues Related To Hmw: Pro-inflammatory or Anti-inflammatorymentioning
confidence: 94%
“…[17] Thus, leptin levels may be a risk factor for the pathogenesis of RA [18]. Olama et al (2012) [15] evaluated the ratio of synovial and serum leptin in patients with RA and found that the local utilization of leptin at the joint cavity has a Records identified through database searching (n = 38)…”
Section: Leptinmentioning
confidence: 99%
“…However, this association was not mediated by the selective effect of HMW adiponectin. [69] Recently, Skalska and Kontny (2016) [18] observed that HMW and MMW adiponectins potentially stimulated the secretion of rheumatoid ASC (adipose-derived stem cells) in patients with RA, but did not exert a strong impact on ASC towards RA-FLS (fibroblast-like synoviocytes) and peripheral blood mononuclear cells. Furthermore, Rho et al (2010) [19] did not find any association between adiponectin levels and insulin resistance or coronary artery calcium score.…”
Section: Mirfeizi Et Al (2014) [30]mentioning
confidence: 99%
“…Adiponectin aggravated bone erosions by promoting osteopontin production in RA synovial tissue, suggesting that adiponectin induced the expression of osteopontin, which in turn recruited osteoclasts [58]. Recently, the effects of adiponectin were assessed on adipose mesenchymal stem cells (ASCs) derived from the infrapatellar fat pad of RA patients [59]. ASCs were stimulated with both low molecular weight (LMW) and high/middle molecular weight (HMW/MMW) adiponectin isoforms.…”
Section: Adipocytokines In Ra: Generality Pathogenic Mechanisms mentioning
confidence: 99%
“…The authors observed that the secretion of proinflammatory mediators was upregulated by HMW/MMW adiponectin, but not by LMW adiponectin. In addition, they observed that the stimulation with HMW/MMW adiponectin reduced the proproliferative effects of ASC-derived soluble factors on RA synovial fibroblasts [59]. Taking together these results, it is possible to suggest a proinflammatory and joint destructive role of adiponectin in RA [5559].…”
Section: Adipocytokines In Ra: Generality Pathogenic Mechanisms mentioning
confidence: 99%